Shade-Tolerant Soybean Reduces Yield Loss by Regulating Its Canopy Structure and Stem Characteristics in the Maize–Soybean Strip Intercropping System - Cheng, Bin; Wang, Li; Liu, Ranjin; Wang, Weibing; Yu, Renwei; Zhou, Tao; Ahmad, Irshan; Raza, Ali; Jiang, Shengjun; Xu, Mei; Liu, Chunyan; Yu, Liang; et al. (Frontiers in Plant Science, 2022)
The shading of maize is an important factor leading to lodging and yield loss of soybean in the maize-soybean strip intercropping system, especially in areas with low solar radiation. This study was designed to explore how shade-tolerant soybean reduces yield loss by regulating its canopy structure and stem characteristics in the maize-soybean strip intercropping system. The soybean cultivars Tianlong No.1 (TL-1, representative of shade-tolerant plants) and Chuandou-16 (CD-16, representative of shade-intolerant plants) were grown in monocropping and intercropping systems from 2020 to 2021 in Chongzhou, Sichuan, China. Regardless of shade-intolerant soybean or shade-tolerant soybean, the canopy and stem of soybean in strip intercropping were weaker than those of corresponding monoculture. But compared with shade-intolerant soybean, the shade-tolerant soybean slightly changed its spatial structure of canopy and stem morphology and physiology in maize-soybean strip intercropping system, especially in the later growth stages. On one hand, the canopy of shade-tolerant soybean showed relatively high transmission coefficient (TC) and relatively low leaf area index (LAI) and mean leaf angle (MLA). On the other hand, the stem of shade-tolerant soybean was obviously stronger than that of shade-intolerant soybean in terms of external morphology, internal structure and physiological characteristics. Additionally, compared with shade-intolerant soybean, shade-tolerant soybean showed higher APnWP (the average net photosynthetic rate of the whole plant) and seed yield in the strip intercropping. The results showed that shade-tolerant soybean increased light energy capture and photosynthesis in the different canopy levels to promote the morphological and physiological development of the stem, and ultimately reduce the yield loss of the strip intercropping system. However, the molecular mechanism of low radiation regulating soybean canopy structure (LAI, TC and MLA) needs further in-depth research to provide theoretical guidance for cultivating plants with ideal canopy shape that can adapt to changing light environment in intercropping system.